Mediastinal schwannoma: A case report - Shrestha, DK; Singh, DR (Journal of Kathmandu Medical College, 2013)
Schwannomas are neurogenic tumours arising from Schwann cells of neural sheath. The peak incidence of these tumours is in 30s to 50s of life, with men and women being equally affected. Schwannoma is an encapsulated tumour which distinguishes it from neurofi broma without encapsulation. With both Schwannoma and neurofi broma, surgical excision results in cure. Our patient, twenty year male, presented with mild, dull aching pain over right antero-lateral chest and non-productive cough associated with breathlessness on physical exertion. Computed tomography of the chest was suggestive of neurogenic tumour (differential diagnoses: ganglioneuroma/ganglioneuroblastoma). The mass was excised via open right posterolateral thoracotomy and was sent for histopathological examination after which he was diagnosed as having Mediastinal Schwannoma. Mediastinal schwannomas, although generally benign and asymptomatic, should be excised upon discovery to prevent the development of life-threatening complications. DOI: http://dx.doi.org/10.3126/jkmc.v1i2.8148 Journal of Kathmandu Medical College, Vol. 1, No. 2, Oct.-Dec., 2012: 106-109